Beyond proofreading: POLD1 mutations as dynamic orchestrators of genomic instability and immune evasion in cancer - Chen, Huiqing; Wei, Jiayu; Tang, Qi; Li, Guohui; Zhou, Yajing; Zhu, Zhen (Frontiers in Immunology, 2025)
DNA polymerase delta (Pol δ) is a cornerstone of genomic stability, orchestrating DNA replication and repair through its catalytic subunit, POLD1. This subunit’s 3’–5’ exonuclease domain proofreads replication errors, ensuring fidelity. However, POLD1 mutations—particularly in this domain—disrupt this function, triggering genomic instability and a hypermutated state in cancers. This review delves into the multifaceted roles of POLD1 mutations, spotlighting their contributions to tumorigenesis and immunotherapy responses. Beyond their established link to syndromes like polymerase proofreading-associated polyposis (PPAP), these mutations unexpectedly enhance tumor immunogenicity in microsatellite-stable (MSS) tumors, previously considered largely resistant to immune checkpoint inhibitors (ICIs). By elevating tumor mutation burden and generating unique mutational signatures (e.g., SBS10d), POLD1 mutations sensitize MSS tumors to ICIs, challenging the dominance of microsatellite instability (MSI) as an immunotherapy predictor. Integrating structural insights, molecular mechanisms, and clinical data, this review positions POLD1 mutations as both a driver of cancer progression and a promising biomarker, redefining therapeutic possibilities in precision oncology.